The Place of Small Business In Afghanistan - Khujamurodov Askarjon Jalolovich; Mamadjanova Tuygunoy Ahmadjanovna; Farzana Mouj Ghafori Ibn Abdul Ghafor (International Journal on Economics, Finance and Sustainable Development, 2021)
The objective of this study was to determine an endeavor to evaluate the challenges faced by Startups and Small Enterprises in Kabul Afghanistan during 2018 . It outlines an approach to learning how startups perceive the impact of input constraints related to market, finance, labor, regulation, technical, etc. on their success. The article recommends specific measures suggested by the related authorities from the government and nongovernment sectors to secure the survival and growth of startups. Prevalence of government regulation, including but not limited to; taxation, bureaucratic licensing, along with complicated procedures are some of the specific challenges faced by Startups and Small business in Kabul.